Profile and factors related to gestational syphilis: integrative review - Vilela, Raíza Martha Lopes dos Santos; Benevenuto, Vitória Carolina Ferreira; Corrêa, Carla Regina de Almeida; Santos, Débora Aparecida da Silva (O Mundo da Saúde, 2024)
Syphilis is a serious public health problem and during pregnancy it can cause complications for the pregnant woman and newborn. The objective was to describe the main factors associated with cases of gestational syphilis in Brazilian women reported in the literature. This is an integrative review of articles published between 2014 and 2023 in the VHL, Scielo and PubMed databases. The descriptors syphilis, pregnancy and epidemiology were used in Portuguese, English and Spanish, applying the Boolean operators AND and OR. After analysis based on the inclusion and exclusion criteria and guiding question, the final sample of twenty articles resulted. The results demonstrated that there is an increasing trend in the incidence of gestational syphilis, in addition, being young, non-white race, low education and income are associated with cases. Inadequate prenatal care and non-treatment of the partner cause an increase in cases of congenital syphilis. It is concluded that greater emphasis is needed on the topic in order to integrate health services, improve flows, reception and assistance, thus strengthening actions aimed at preventing, controlling and reducing cases of gestational syphilis.